Patients with Coronary Artery Disease who Present with Chest Pain Have Significantly Elevated Platelet Contractile Force and Clot Elastic Modulus - Krishnaswami, Ashok; Carr, Marcus E., Jr.; Jesse, Robert L.; Kontos, Michael C.; Minisi, Anthony J.; Ornato, Joseph P.; Vetrovec, George W.; Martin, Erika J. (Thrombosis and Haemostasis, 2002)
Rapid laboratory markers that correlate with patient risk would facilitate the decision making regarding admission of patients with chest pain (CP). Platelet contractile force (PCF) and clot elastic modulus (CEM) are elevated in patients undergoing coronary bypass grafting. This study assessed PCF, CEM, and platelet aggregation in patients presenting to the emergency department with chest pain (CP). Results were compared with fifty normal controls. Both the total group of CP patients (n = 100) and the subset of patients (n = 36) with documented coronary arterys disease (CAD) had significantly elevated PCF and CEM, and significantly decreased platelet aggregation relative to normal (p <0.001 for the total group, p <0.008 for patients with CAD). Patients with electrocardiographic evidence of ischemia had the highest PCF and CEM values of any patient group. Increased PCF and CEM were not due to higher platelet counts, and PCF did not differ by race.
Keywords: Coronary artery disease; angina; platelet contractile force; platelet aggregation